Facilitating Ambulatory Electronic Health Record System Implementation: Evidence from a Qualitative Study. (20th October 2013) - McAlearney, Ann Scheck; Sieck, Cynthia; Hefner, Jennifer; Robbins, Julie; Huerta, Timothy R.
Abstract : Background . Ambulatory care practices have increasing interest in leveraging the capabilities of electronic health record (EHR) systems, but little information is available documenting how organizations have successfully implemented these systems. Objective . To characterize elements of successful electronic health record (EHR) system implementation and to synthesize the key informants' perspectives about successful implementation practices. Methods . Key informant interviews and focus groups were conducted with a purposive sample of individuals from US healthcare organizations identified for their success with ambulatory EHR implementation. Rigorous qualitative data analyses used both deductive and inductive methods. Results . Participants identified personal and system-related barriers, at both the individual and organization levels, including poor computer skills, productivity losses, resistance to change, and EHR system failure. Implementation success was reportedly facilitated by careful planning and consistent communication throughout distinct stages of the implementation process. A significant element of successful implementation was an emphasis on optimization, both during "go-live" and, subsequently, when users had more experience with the system. Conclusion . Successful EHR implementation requires both detailed planning and clear mechanisms to deal with unforeseen or unintended consequences. Focusing on user buy-in early and including plans for optimization can facilitate greater success.